Taking nutrition into account within the life cycle assessment of food products. (15th April 2017) - Saarinen, Merja; Fogelholm, Mikael; Tahvonen, Raija; Kurppa, Sirpa
Abstract: The environmental impact of food is mostly assessed on a weight basis, although nutrition is the key function of food. This paper develops a methodology to combine nutritional and environmental aspects within the food life cycle assessment (LCA). There are two approaches in the paper: The first considers individual nutrients separately and uses mass-based functional units (FU), and the second one considers multiple recommended nutrients at the same time by using a nutrient index as the FU, and considers nutrients to be limited as a separate measure. The target was to find a basis for differentiation between sustainable and unsustainable foods. The nutrient indexes utilized are a general index NR9 from the NRF index family, a product-group-specific index for protein sources, FNIprot7, which was formed during the study, and LIM3 and LIM2 for nutrients to be limited. In addition, the role of reference flow (RF) is highlighted. The methodological approaches are demonstrated by an assessment of 29 food products. The product systems included all main stages of the life cycle from primary production to consumption. The second approach is proposed to be used as a general method for food LCA to take nutritional aspects into account, while the first approach can be useful when considering the relative climate impact of foods in a situation of scarce nutrients with limited sources, or a deficiency of certain nutrients.